Osteological development of the larvae and juveniles of Thryssa kammalensis (Clupeiformes: Engraulidae) from the Southwestern Coasts of Korea - Hyeon-Jun Ryu; Se Hun Myoung; Sang-Chul Yoon; Jeong-Hoon Lee; Jin-Koo Kim (Zoomorphology, 2026)

Improvement of color purity and operational lifetime for PhOLEDs based on tetradentate Pt (II) complex - Hyunmin Cho; Jinwoong Hong; Young Hun Jung; Se Chan Cha; Mi Young Chae; Soon-Ki Kwon; Yun-Hi Kim; Jang Hyuk Kwon (Chemical Engineering Journal, 2026)

Multimodal Graphical Network Analysis of Small-for-Gestational-Age in Preterm Infants: Integrating Neonatal Brain Volume, Structural Connectivity, and Early Neurodevelopmental Outcome - Se Hyun Lee; Yong Hun Jang; Hyuna Kim; Gang Yi Lee; Hyun Ju Lee; Hyun Ho Kim (Annals of Biomedical Engineering, 2026)
Purpose Infants born Small-for-gestational-age (SGA) face heightened risks for cognitive and language impairments. The neurobiological mechanisms underlying these deficits remain unclear. This study aimed to identify multimodal neuroimaging biomarkers associated with fetal growth restriction and to characterize network-level associations linking SGA to early neurodevelopmental vulnerability using a data-driven graph-based framework. Methods In this prospective cohort of 186 preterm infants, near-term brain magnetic resonance imaging (MRI) and Bayley-III developmental assessments were analyzed. Multimodal imaging features—including volumetric indices from T2-weighted MRI and diffusion metrics from diffusion tensor imaging—were integrated with perinatal data. A sparse partial-correlation network was estimated using the Graphical Lasso algorithm (λ optimized via cross-validation) to infer conditional dependencies among features. Variables directly connected to birthweight Z-scores were identified as candidate biomarkers and validated for SGA classification and developmental outcomes using logistic regression and correlation analyses. Results Network analysis identified eight neuroanatomical correlates of birthweight Z-scores, including increased cerebrospinal fluid (CSF) volume; elevated axial, mean, and radial diffusivity in the left inferior longitudinal fasciculus (ILFL); higher axial diffusivity in the inferior fronto-occipital fasciculus; and altered degree centrality in the right precentral and posterior cingulate cortices (PCC). Logistic regression revealed CSF volume and ILFL diffusivity as independent predictors of SGA. Infants with language delay showed trend-level increases in ILFL diffusivity and reduced PCC centrality after FDR correction, suggesting possible associations between microstructural and connectomic alterations and language vulnerability. Conclusion By integrating volumetric and diffusion MRI with graph-based modeling, this study uncovers latent neurobiological markers of SGA and provides clinically interpretable biomarkers for early risk stratification and individualized intervention.

White ginseng ethanol extract inhibits melanogenesis in B16F10 cells by regulating the microphthalmia-associated transcription factor/tyrosinase pathway - Min Jung Kim; Ye Jin Yang; Ji Woong Heo; Han Nim Choi; Chae Un Lim; Se Hyo Jeong; Hun Hwan Kim; Gon Sup Kim; Young Hun Kim; Ju-Hye Yang; Kwang Il Park (Molecular & Cellular Toxicology, 2026)

Thermal-responsive nanohole surface with active antibacterial properties against Staphylococcus aureus - Hee-Kyeong Kim; Se Hun Kim; Rigoberto Lopez Reyes; Dongyan Chen; Batzorig Buyantogtokh; Seungbum Hong; Young-Sam Cho; Hyun-Ha Park (Chemical Engineering Journal, 2026)

Intranasal nanophotosensitizer enables safe and broad-spectrum photodynamic inactivation of respiratory viruses - Sunmi Han; Assel Seitkazina; Jeongyun Heo; Se-young Kim; SuJin Kim; Sung-Ho Jeon; Yung Hun Park; Taehun Lim; Bohyeon Kim; Shivani Rajoriya; Quy Son Luu; Youngbok Lee; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

Ellagic acid treatment during in vitro maturation of porcine oocytes improves development competence after parthenogenetic activation and somatic cell nuclear transfer - Han-Bi Lee; Seung-Eun Lee; Min-Jee Park; Dong-Hun Han; Eun-Seo Lim; Bokyeong Ryu; Eun-Young Kim; Se-Pill Park (Theriogenology, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

A stress-adaptive interlinked 3D network binder for silicon anodes via tailored chemical bonds and conformation of functionalized poly(vinylidene fluoride) (PVDF) terpolymers - Young Je Kwon; Ji-Oh Kim; E. Vivek; Eunji Kim; Se Hun Kim; Taekyun Kwon; Eunyoung Lim; Seongwook Chae; Minjoon Park; Youngho Eom; Ji-Hoon Baik; Jin Hong Lee; et al. (Chemical Engineering Journal, 2024)

Comparison of photosynthetic efficiency and growth characteristics of paprika in semi-closed vs. conventional greenhouses - Eun ji Kim; Beom Seon Lee; Yong Hwan Jeon; Se Hun Ju; Yoon Go; Jin Sub Park; Joonwoo Lee; Huijun Yang; Haeyoung Na (Horticulture, Environment, and Biotechnology, 2023)

Personal exposure of PM2.5 and metabolic syndrome markers of pregnant women in South Korea: APPO study - Yeonseong Jeong; Sunwha Park; Eunjin Kwon; Young Min Hur; Young-Ah You; Soo Min Kim; Gain Lee; Kyung A. Lee; Soo Jung Kim; Geum Joon Cho; Min-Jeong Oh; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2023)
We examined the association between exposure to PM 2.5 , focused on individual exposure level, and metabolic dysfunction during pregnancy. APPO study (Air Pollution on Pregnancy Outcome) was a prospective, multicenter, observational cohort study conducted from January 2021 to March 2023. Individual PM 2.5 concentrations were calculated using a time-weighted average model. Metabolic dysfunction during pregnancy was assessed based on a modified definition of metabolic syndrome and its components, accounting for pregnancy-specific criteria. Exposure to PM 2.5 during pregnancy was associated with worsened metabolic parameters especially glucose metabolism. In comparison to participants exposed to the low PM 2.5 group, those exposed to high PM 2.5 levels exhibited increased odds of gestational diabetes mellitus (GDM) after adjusting for confounding variables in different adjusted models. Specifically, in model 1, the adjusted odds ratio (aOR) was 3.117 with a 95% confidence interval (CI) of 1.234–7.870; in model 2, the aOR was 3.855 with a 95% CI of 1.255–11.844; in model 3, the aOR was 3.404 with a 95% CI of 1.206–9.607; and in model 4, the aOR was 2.741 with a 95% CI of 0.712–10.547. Exposure to higher levels of PM 2.5 during pregnancy was associated with a tendency to worsen metabolic dysfunction markers specifically in glucose homeostasis. Further research is needed to investigate the mechanisms underlying the effects of ambient PM 2.5 on metabolic dysfunction during pregnancy.

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

Wintertime sea surface temperature variability modulated by Arctic Oscillation in the northwestern part of the East/Japan Sea and its relationship with marine heatwaves - Se-Yong Song; Yoo-Jun Kim; Eun-Joo Lee; Sang-Wook Yeh; Jae-Hun Park; Young-Gyu Park (Frontiers in Marine Science, 2023)
The northwestern part of the East/Japan Sea (EJS) is a region with large sea surface temperature (SST) variability and is known as a hotspot of marine heatwaves (MHW) stress for marine environments that peaked in boreal winter (January-February-March). This could have profound impacts on the marine ecosystems over the EJS. Here, we used a set of high-resolution satellite and reanalysis products to systematically analyze the spatiotemporal SST variations and examine their linkage to a large-scale mode of climate variability, such as the Arctic Oscillation (AO). The results show that AO-related wind forcing modulates the SST variability over the EJS via the oceanic dynamic adjustment processes. In particular, the abnormally warm SSTs in the northwestern part of the EJS are driven by the anomalous anticyclonic eddy-like circulation and Ekman downwelling during a positive AO phase. This physical linkage between a positive AO and the abnormally warm SST could be conducive to MHW occurrences in the EJS as in the extremely positive AO event during the winter of 2020. These results have implications that the MHW occurrences in the EJS could be amplified by natural climate variability along with long-term SST warming.

Variations in food resource usage among eight fish species inhabiting inside and outside Jinju Bay, Korea - Se Hun Myoung; Jin-Koo Kim; Seok Nam Kwak; Joo Myun Park (Environmental Biology of Fishes, 2022)

Treatment with silicon fertilizer induces changes in root morphological traits in soybean (Glycine max L.) during early growth - Yong Suk Chung; Se-Hun Kim; Chang- Wook Park; Chae -In Na; Yoonha Kim (Journal of Crop Science and Biotechnology, 2020)

Prolonged shedding of type 55 human adenovirus in immunocompetent adults with adenoviral respiratory infections - Kyungmin Huh; Inseon Kim; Jaehun Jung; Ji Eun Lee; Byung Woo Jhun; Se Hun Gu; Dong Hyun Song; Eun Young Lee; Ho Jung Jeong; Hongseok Yoo (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Size-dependent characteristics of diurnal particle concentration variation in an underground subway tunnel - Sang-Hee Woo; Jong Bum Kim; Gwi-Nam Bae; Moon Se Hwang; Gil Hun Tahk; Hwa Hyun Yoon; Soon-Bark Kwon; Duckshin Park; Se-Jin Yook (Environmental Monitoring and Assessment, 2018)

Calibration of the Pyranometer Sensitivity Using the Integrating Sphere - Bu-Yo Kim; Kyu-Tae Lee; Il-Sung Zo; Sang-Ho Lee; Hyun-Seok Jung; Se-Hun Rim; Jeong-Pil Jang (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Thermoresponsive and Biodegradable Amphiphilic Block Copolymers with Pendant Functional Groups - Bo Keun Lee; Jung Hyun Noh; Ji Hoon Park; Seung Hun Park; Jae Ho Kim; Se Heang Oh; Moon Suk Kim (Tissue Engineering and Regenerative Medicine, 2018)

Correction to: Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Correction to: Development of 21 polymorphic microsatellite markers for the black-banded sea krait, Laticauda semifasciata (Elapidae: Laticaudinae), and cross-species amplification for two other congeneric species - Young Se Hyun; Il-Hun Kim; Ha Yeun Song; Daesik Park; Mamoru Toda; Tein-Shun Tsai; Hye Suck An (Genes & Genomics, 2018)

Surface Downward Longwave Radiation Retrieval Algorithm for GEO-KOMPSAT-2A/AMI - Seo-Hee Ahn; Kyu-Tae Lee; Se-Hun Rim; Il-Sung Zo; Bu-Yo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Retrieval Algorithm for Broadband Albedo at the Top of the Atmosphere - Sang-Ho Lee; Kyu-Tae Lee; Bu-Yo Kim; ll-Sung Zo; Hyun-Seok Jung; Se-Hun Rim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of 21 polymorphic microsatellite markers for the black-banded sea krait, Laticauda semifasciata (Elapidae: Laticaudinae), and cross-species amplification for two other congeneric species - Young Se Hyun; Il-Hun Kim; Ha Yeun Song; Daesik Park; Mamoru Toda; Tein-Shun Tai; Hye Suck An (Genes & Genomics, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Population structure of the Korean gizzard shad, Konosirus punctatus (Clupeiformes, Clupeidae) using multivariate morphometric analysis - Se Hun Myoung; Jin-Koo Kim (Ocean Science Journal, 2016)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Genetic diversity and population structure of the gizzard shad, Konosirus punctatus (Clupeidae, Pisces), in Korean waters based on mitochondrial DNA control region sequences - Se Hun Myoung; Jin-Koo Kim (Genes & Genomics, 2014)

Two new records of Valenciennea helsdingenii (Perciformes: Gobiidae) and Chromis margaritifer (Perciformes: Pomacentridae) from Jeju Island, Korea - Jung-Goo Myoung; Se Hun Myoung; In-Seo Hwang; Byung-il Kim; Jin-Koo Kim (Ocean Science Journal, 2014)

Carpesium abrotanoides extract inhibits cyclooxygenase-2 expression induced by toll-like receptor agonists - Do-Won Jeong; Eun-Kyeong Lee; Chung-Ho Lee; Se Jin Lim; Gyo-Jeong Gu; Ji Hun Paek; Songmun Kim; Soon Sung Lim; Hyung-Sun Youn (Toxicology and Environmental Health Sciences, 2013)

Antiviral Effects of Sulfated Exopolysaccharide from the Marine Microalga Gyrodinium impudicum Strain KG03 - Joung Han Yim; Sung Jin Kim; Se Hun Ahn; Chong Kyo Lee; Ki Tae Rhie; Hong Kum Lee (Marine Biotechnology, 2004)